Longing for Home and Nurturing Hope: International PhD Students’ Experiences of Disrupted Mobility during COVID-19 (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
This essay explores the emergent precarity of not being able to go home of a Vietnamese doctoral student in New Zealand when the COVID-19 pandemic hit the globe in early 2020, resulting in banned international travel. The longing for home became a new source of strength for the student to grow more resilient and calm amid the global crisis and reinforced her sense of belonging to both the home and host countries.